A Distributed Effects Perspective of Dimensionally Defined Psychiatric Disorders: And Convergent Versus Core Deficit Effects in ADHD - Hale, T. Sigi (Frontiers in Psychiatry, 2014)
The focus of psychiatric and psychological research has arguably shifted from brain damage and psychosis to more common forms of psychopathology that reflect extremes variants of otherwise normal cognitive and behavioral characteristics. Now, in addition to trying to understand overtly damaged brain function (flat tire effects), we are also seeking to understand liabilities associated with non-optimized, but otherwise intact, cognitive and behavioral abilities (poor tuning effects). This shift has pushed us to evolve our investigational strategies to more broadly consider whole-brain integrated brain-systems, as well as seek to develop more specific quantifiable indicators of impoverished brain function and behavior. This paper discusses such challenges in relation to dimensionally defined psychiatric disorders and presents a novel whole-brain integrated perspective of ADHD brain function pathology.